(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
This community service activity aims to support the Savings and Loan Cooperative in Bambe Village, Driyorejo District, in addressing problems of inefficient manual recording, potential errors, and suboptimal transparency of financial information for members. The proposed solution is the development of a web-based application that includes membership management, recording of savings and loan transactions, interest calculation, real-time financial reporting, transaction notifications, and automatic calculation of Operating Surplus (SHU). The implementation method consists of six stages: problem analysis, collaborative solution design with partners, system implementation, training and assistance, monitoring and evaluation, and report preparation and publication. The results show that the application is able to improve cooperative administrative efficiency, accelerate the reporting process, and increase the openness of information access for members. Based on questionnaire results from 30 respondents, the level of user satisfaction falls into the very good category with an average score of 4.5 out of 5. Further evaluation indicates the need to improve members’ understanding of application usage, leading to additional training and system improvements based on user feedback. Future development is directed toward the integration of digital payment systems.